1984
DOI: 10.1192/bjp.144.5.453
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorder in Pregnancy and the First Postnatal Year

Abstract: We interviewed 128 women regularly during pregnancy and the first postnatal year. Psychiatric interviews identified eight 'cases' of psychiatric disorder (6 per cent) in early pregnancy and twenty 'cases' (16 per cent) at six weeks after birth. Postnatal affective disorder, which accounted for 15 of these cases, was significantly associated with dissatisfaction with the marital relationship and also with previous psychiatric history. The implications of the term 'postnatal depression' are considered in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
206
3
15

Year Published

1991
1991
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 439 publications
(244 citation statements)
references
References 12 publications
20
206
3
15
Order By: Relevance
“…Chronic anxiety and stress lead to a decrease in platelet peripheral benzodiazepine receptor density (Weizman et al 1987;Weizman and Gavish 1993). Pregnancy and the postpartum period are sometimes accompanied by anxiety and depression (Watson et al 1984). However, psychiatric evaluation of all the women in the present study revealed no signs of anxiety disorder or major depression, and no statistically significant differences in Hamilton anxiety and depression rating scores were detected among the various groups (although an increase of 36% in anxiety scores occurred at the third trimester).…”
Section: Discussioncontrasting
confidence: 57%
“…Chronic anxiety and stress lead to a decrease in platelet peripheral benzodiazepine receptor density (Weizman et al 1987;Weizman and Gavish 1993). Pregnancy and the postpartum period are sometimes accompanied by anxiety and depression (Watson et al 1984). However, psychiatric evaluation of all the women in the present study revealed no signs of anxiety disorder or major depression, and no statistically significant differences in Hamilton anxiety and depression rating scores were detected among the various groups (although an increase of 36% in anxiety scores occurred at the third trimester).…”
Section: Discussioncontrasting
confidence: 57%
“…Because many researchers argue that there is little to distinguish PPD from depression occurring at other times (O'Hara and Zekoski 1988;Watson et al 1984;Whiffen 1991Whiffen , 1992Whiffen and Gotlib 1993), any conclusion reached for PPD also may be applicable to depression in general. The ability to defect from costly ventures has obvious utility, and many researchers argue that this ability is one of the foundations of cooperative behavior-cooperation cannot evolve if individuals have no means to renegotiate or terminate costly relationships (for a review, see Axelrod and Dion 1988).…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological studies have indicated that 10-15% of mothers suffer from a depressive disorder in the postpartum period (Kumar and Robson 1984;Watson et al 1984;Cooper et al 1988;Cox et al 1993). Behavioural disturbances and cognitive deficits during childhood are common among the children of such depressed mothers (Wrate et al 1985;Cogill et al 1986).…”
Section: Introductionmentioning
confidence: 99%